Cytotoxic steroids from the mushroom Ganoderma australe collected in Laos - Keomanykham, Onesy; Khamko, Vong Anatha; Keorodom, Bounpong; Khemmarath, Sitha; Quang, Dang Ngoc (Vietnam Journal of Chemistry, 2016)
Five steroids named stigmasterol (1), ergosterol peroxide (2), ganodertriol M (3), lucidumol B (4) and kansenone (5) were purified from the ethyl acetate extract of fruit bodies of the mushroom Ganoderma australe collected in Savannakhet province, Laos. Their structures were characterized by the combination of HR-MS, one and two dimensional NMR spectroscopic analyses. In addition, ergosterol peroxide and kansenone showed good cytotoxicity against four cancer cell lines, KB (human epidermal carcinoma), MCF7 (human breast carcinoma), SK-LU-1 (human lung carcinoma) and Hep-G2 (hepatocellular carcinoma). This is the first report on the chemical constituents and cytotoxic steroids from Ganoderma sp. in Laos